Fragmented care in the era of limited work hours: a plea for an explicit handover curriculum. Issue 1 (21st November 2012) - Wohlauer, Max
Abstract : The current challenge in surgical residency education, preserving a sense of accountability in an era of limited work hours and multiple transitions of care, can be accomplished through the promotion of effective handovers. Approaches include increasing the transparency of handovers, enhancing the 'situational awareness' of individuals involved, and incorporating narratives and social interactions, and expanding common ground among professionals who collectively have responsibility for patient care. Done well, handovers can preserve the physician-patient relationship and provide a continuity bridge during a vulnerable time for patients.